Leveraging Local Historical Heritage to Strengthen Students' National Insight and Nationalism - Aulia Mutiara Putri; Dyah Kumalasari; Dimas Aditia (STAI Hubbulwathan Duri, 2025)
This study investigates how local cultural heritage sites in Metro City—specifically the Dokterswoning House and Santa Maria Hospital—contribute to fostering national insight and strengthening nationalism. As historical assets, these sites hold educational value and play a crucial role in shaping national identity and public appreciation for historical and cultural values.A qualitative research approach was employed, using in-depth interviews to gather insights from local residents, site managers, and historians. The study aimed to explore community perceptions and experiences regarding the educational and nationalistic potential of these heritage sites. Data were analyzed through qualitative descriptive methods to examine the link between heritage use and national awareness.Findings indicate that the Dokterswoning House and Santa Maria Hospital serve as effective mediums for historical education, promoting national values through organized educational programs, heritage tourism, and active community participation. These initiatives have enhanced public awareness of national identity and deepened emotional ties to the nation.The integration of local heritage into community life not only preserves cultural memory but also cultivates patriotism and civic responsibility. Familiarity with historical narratives associated with these sites was found to significantly influence individuals’ sense of national belonging.This research highlights the strategic role of cultural heritage in advancing national insight at the local level. It advocates for sustained heritage management and educational programming as essential tools for nation-building and identity formation.